Eksistensi Perempuan Dalam Dakwah Kontemporer Perspektif Al-Qur’an dan Hadis - Alfiyah, Avif; Ahlan, Ahlan; Adila, Fadia (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2022)
This article aims to find out the role of woman in the world of dakwah. Woman in Islam have the same right in preaching but what makes the difference is the level or the amount Islam places woman in this very honorable position because woman have tasks that can not be done by man, for example, conceiving, giving birth and breastfeeding, all of which risk their lives in their practice. This article discusses two roles of woman in the contemporary era as preachers. First, the role of woman in the view of Islam that woman occupy an honorable and noble position. Islam does not differentiate between man and woman for dakwah matters such as admonishing amr ma’ruf and nahi munkar. And second, the role of woman in dakwah is in accordance with the level of their ability to do amr ma’ruf nahi munkar. it can preach at home with their families, it can preach on the go every where. This research is qualitative descriptive study with a library research approach.